Silver(I) and mercury(II) complexes of meta- and para-xylyl linked bis(imidazol-2-ylidenes) - Baker, M.; Brown, David; Haque, R.; Skelton, B.; White, A. (Springer Netherlands, 2009)
Mononuclear silver and mercury complexes bearing bis-N-heterocyclic carbene (NHC) ligands withlinear coordination modes have been prepared and structurally characterised. The complexes form metallocyclic structures that display rigid solution behaviour. A larger metallocycle of the form [L2Ag2]2+ [where L = parabis(N-methylimidazolylidene)xylylene] has been isolated from the reaction of para-xylylene-bis(N-methylimidazolium) chloride and Ag2O. Reaction of silver- and mercury-NHC complexes with Pd(NCCH3)2Cl2 affords palladium-NHC complexes via NHC-transfer reactions, the mercury case being only the second example of a NHC-transfer reaction using a mercury-NHC complex.